The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/pc.22736
|View full text |Cite
|
Sign up to set email alerts
|

Physical, mechanical, and water absorption behavior of coir/glass fiber reinforced epoxy based hybrid composites

Abstract: Fiber reinforced polymer composites has been used in a variety of application because of their many advantages such as relatively low cost of production, easy to fabricate, and superior strength compare to neat polymer resins. Reinforcement in polymer is either synthetic or natural. Synthetic fiber such as glass, carbon, etc. has high specific strength but their fields of application are limited due to higher cost of production. Recently there is an increase interest in natural composites which are made by rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 16 publications
4
42
0
Order By: Relevance
“…It is observed that the deformation depth increases for water-immersed specimen compared to dry one, due to the hydrophilic nature of fibers and led to the deformation of a weak fiber-matrix interface. The results also agree well with the results of Al-Mosawi Ali [10] and by other researchers working with natural fiber based composites [11,12]. …”
Section: Hardness Density and Void Formationsupporting
confidence: 82%
See 2 more Smart Citations
“…It is observed that the deformation depth increases for water-immersed specimen compared to dry one, due to the hydrophilic nature of fibers and led to the deformation of a weak fiber-matrix interface. The results also agree well with the results of Al-Mosawi Ali [10] and by other researchers working with natural fiber based composites [11,12]. …”
Section: Hardness Density and Void Formationsupporting
confidence: 82%
“…The cause of the reduction of strength may be fiber entanglement. This may be observed by the results and consequence drawn by literature reference [13][14].…”
Section: Figure 2: Variation In Tensile Properties With the Effect Ofsupporting
confidence: 62%
See 1 more Smart Citation
“…On the other hand, the properties such as, biodegrability, cheapness, accesibility, low density and high specific properties make natural fibers (banana, cotton, jute, sisal, etc.) advantageous over man-made fibers [4,6]. Natural fiber reinforced composites have good thermal and acoustic insulating properties and they are resistant to fracture [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rezultati so pokazali, da vrsta in razporeditev ojačitvenega materiala pomembno vplivata na dinamične mehanske lastnosti kompozitnih vzorcev. Ključne besede: tekstilni kompoziti, dinamična mehanska analiza, termogravimetrična analiza, dinamična kalorimetrija e advantageous properties of E-glass bres that make them preferable materials for composite structures are their high damping characteristics, lightweight, low cost, high strength, good resistance to corrosion and excellent insulation properties [5][6][7][8]. Dynamic mechanical analysis (DMA) is a technique that measures both the mechanical and viscoelastic properties of materials [9].…”
Section: Izvlečekmentioning
confidence: 99%